Enhance the performance of 3-phase induction motors with the utilization of a 9-phase winding design - Zulkarnaini, Zulkarnaini; Bandri, Sepannur; Erhaneli, Erhaneli; Anthony, Zuriman; Warmi, Yusreni; Rachman, Arfita Yuana Dewi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
Because of its sturdy design, affordability, and convenience of use, the three phase induction motor is a common kind of electric motor, especially in the industrial sector. This motor design is still being improved to make it work better. For example, permanent magnets are being added to the rotor, control systems are getting better, the number of phases is being increased, and motor winding designs are developing. Nevertheless, the creation of the motor winding design is the least expensive aspect of all these endeavors. By creating a nine-phase winding configuration with a three-layer design in the motor, this study aims to enhance the performance of a three-phase induction motor. This study examined output power, speed, mechanical torque, and motor efficiency in a 3-phase system operation. The study's results indicated that the new design motor worked better, with higher output power (4.27%), rotor speed (0.61%), and mechanical torque (3.47%), despite a minor reduction in efficiency relative to conventional 3-phase induction motors (-0.24%).